Understanding Customer Satisfaction with Self-Service Technologies (SSTs) in a Retail Setting - WANG, Yan (2014)
Self-Service Technologies (SSTs) are increasingly changing the way customers interact with firms to create service outcomes. Self-checkout installations, as one of the most common SSTs, are being tested by major supermarket chains in retail industries across the world. However, the success of the new technology from the consumer's perspective is not yet clear. The present study investigates the determinants of consumer satisfaction for using self-checkouts with a view to addressing these practitioner issues. In addition, the study advances theory on consumer behavioural intentions related to SSTs in general. Factors driving preference or avoidance of self-checkouts include attributes of service quality, perceived value, customer attitude and demographics. A quantitative research method is used to investigate these issues and offers richer findings through SPSS analyses. Implications are discussed for managerial strategy as well as limitations for future research.